Strengthening Responsible AI Literacy through TPACK and Prompt Engineering Training for High School Teachers to Enhance Digital Pedagogical Competence at SMA At Thohiriyyah, Semarang - Fahmi, Amiq; Sugiarto, Edi; Pramudi, Y. Tyas Catur; Mulyanto, Edy (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the Responsible AI Literacy of high school teachers at SMA At Thohiriyyah, Semarang City, in alignment with the Indonesian Joint Decree of Seven Ministers (SKB 7 Menteri), which emphasizes strengthening teachers’ digital and pedagogical competencies in the era of AI-driven education. The program was implemented through In-House Training (IHT) based on the Technological Pedagogical and Content Knowledge (TPACK) framework and Prompt Engineering, involving 18 teachers. The implementation consisted of three stages—preparation, implementation, and evaluation—and employed pre-test and post-test instruments complemented by qualitative observations. Data were analyzed using quantitative and qualitative approaches, with triangulation applied to enhance the validity of the findings. The results showed a substantial improvement, with the average pre-test score increasing from 72.3 to 93.6 in the post-test, representing a 29.4% improvement. Qualitative findings indicated that participants actively engaged in discussions, hands-on practice, and reflective activities, and successfully developed AI-assisted teaching modules, student worksheets, and assessment instruments that support the deep learning paradigm. These findings suggest that TPACK- and Prompt Engineering-based In-House Training was effective in strengthening teachers’ Responsible AI Literacy across technical, pedagogical, and ethical dimensions and has the potential to be adopted as a sustainable professional development strategy for educators in the digital era.